Vehicle dynamics modelling and validation for hardware-in-the-loop testing of electronic stability control - Emirler, Mümin Tolga; Uygan, İsmail Meriç Can; Gelbal, Şükrü Yaren; Gözü, Murat; Böke, Tevfik Ali; Güvenç, Bilin Aksu; Güvenç, Levent (Inderscience Publishers, 2016)
Hardware-in-the-loop (HiL) simulation is used to test code changes in automotive control systems for component tests and for fault testing. A realistic and validated vehicle dynamic model needs to be used in the simulations. The experimental and simulated results should exhibit a close match in a validation study. The development of a validated CarSim model of a light commercial vehicle for use in HiL simulation is presented in this paper. A CarSim dynamics model has been prepared for a light commercial vehicle and validated using driving test data obtained on a test track. The HiL simulator developed for testing the electronic stability control unit of this vehicle is presented along with results of an exemplary HiL simulation.